Pemanfaatan Media Virtual Reality Berbasis Kearifan Lokal melalui Alat Musik Sampe untuk Meningkatkan Kemampuan Berpikir Kritis - Lia Anggraeni, M.Pd; Henny Puspitasari; Eti Sukadi (Kappa Journal, 2021)
The demand for implementing industrial revolution education 4.0 is the use of information technology in the learning process. Virtual Reality (VR) media in learning is one of the uses of technology in its implementation. Utilization of VR media must also be accompanied by including the role of local wisdom by using musical instruments sampe. It is hoped that through learning using VR media based on local wisdom it can improve students' critical thinking skills. This study aims to improve critical thinking skills and instill the value of local wisdom in students. The method used in this research is an experimental method with the form of pre-experimental research design and one-group pretest-posttest design research design. Samples were selected using probability sampling techniques. The research sample was the second semester students of the Physics Education Study Program of IKIP PGRI Pontianak. The instrument used was a critical thinking skills test and a questionnaire. This study obtained qualitative and quantitative data, where quantitative data were analyzed using statistical analysis t test to see the increase in students' critical thinking skills. Based on the analysis of the results of the critical thinking test, it was concluded that there was an increase in students' critical thinking skills using VR media based on local wisdom.